2014
DOI: 10.1186/cc13823
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit depth of sleep: proof of concept of a simple electroencephalography index in the non-sedated

Abstract: IntroductionIntensive care unit (ICU) patients are known to experience severely disturbed sleep, with possible detrimental effects on short- and long- term outcomes. Investigation into the exact causes and effects of disturbed sleep has been hampered by cumbersome and time consuming methods of measuring and staging sleep. We introduce a novel method for ICU depth of sleep analysis, the ICU depth of sleep index (IDOS index), using single channel electroencephalography (EEG) and apply it to outpatient recordings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…No significant differences were detected for AUCs for any other spectral power frequency analyzed between the two groups (see Table 4 ). Delta and gamma power oscillated reciprocally within each SWS cycle with delta power increasing and gamma power decreasing from the start to end of each SWS cycle in both groups similar to previously reported findings [ 36 , 37 ]. In addition, AUCs for gamma power also showed non-significant differences with similar trends along the AP axis in RTT group that were not significantly different from the control group during SWS sleep ( Fig 2C , Table 4 ).…”
Section: Resultssupporting
confidence: 91%
“…No significant differences were detected for AUCs for any other spectral power frequency analyzed between the two groups (see Table 4 ). Delta and gamma power oscillated reciprocally within each SWS cycle with delta power increasing and gamma power decreasing from the start to end of each SWS cycle in both groups similar to previously reported findings [ 36 , 37 ]. In addition, AUCs for gamma power also showed non-significant differences with similar trends along the AP axis in RTT group that were not significantly different from the control group during SWS sleep ( Fig 2C , Table 4 ).…”
Section: Resultssupporting
confidence: 91%
“…Given the high interscorer reproducibility of this method, these measurements could facilitate the sharing of sleep quantification across ICUs. Sleep continuity might be a useful measure of sleep quality in all patients in whom the distribution of sleep episode duration could be reliably determined; sleep continuity could be calculated using the automated EEG analysis recently reported in ICU patients [ 40 ]. However, before being considered as an effective alternative metric in the study of sleep in ICUs, sleep continuity measurements need to be replicated and tested in critically ill patients with atypical sleep, in patients with a high severity of illness and in patients receiving sedatives.…”
Section: Discussionmentioning
confidence: 99%
“…5 As part of a pilot study, we too found severely fragmented sleep and EEG activity that suggest heightened arousal and signs of sleep deprivation. 6 Patients admitted to an ICU are exposed to several intrinsic and extrinsic sleep-disrupting factors, which were described previously in more detail by Le Guen and colleagues. 7 A multitude of these factors, most of them interdependent, likely causes the disrupted sleep observed in the ICU.…”
Section: Key Pointsmentioning
confidence: 99%